ANALISIS BIBLIOMETRIK DALAM TREND PENELITIAN KEWIRAUSAHAAN PEDESAAN (Bibliometric Analysis in Rural Entrepreneurship Research Trends) - Putra Irwandi; Bunga Wirda; Indira Rosandry; Burhanuddin Burhanuddin (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2024)
Villages are one of the strategic goals in national development. Changes in the era of globalization and socio-economics have created a variety of problems faced by villages. Villages provide potential as a source of food, a major center for energy and the environment as well as producing productive human resources and driving cities. So in this context, rural entrepreneurship emerges as the main driver for reviving and developing local economic potential, as well as ensuring social and economic inclusion for rural communities based on rural potential and wisdom. This research aim on presenting and analyzing research trends in rural entrepreneurship using a bibliometric approach. Data analysis used the Scopus database with 128 articles analyzed using bibliometrics. From the results of the analysis, it was found that there was main information available from the document, source interaction, title and author, three fields plot diagram, relevant article sources, countries producing the most articles, dominating keywords, conceptual structure, thematic map, and thematic evolution. Through the use of this method, the authors hope to provide in-depth insight into recent developments in rural entrepreneurship research, as well as provide valuable insights for researchers, practitioners, and policy makers to shape future research directions and interventions.Keywords: Bibliometrics, R-studio, visualization